ETHNIC IDENTITY AND CONFLICT: LESSONS FROM THE KOSOVO CRISIS - Negash, Mossa Hussen (European Scientific Journal, ESJ, 2015)
Ethnic identity and conflict often inter-married in countries where diversities on such grounds were seen as a threat. Conflicts in the post cold war period attained a new dimension. The Balkan region has been one of the most conflict prone regions in the world where conflict arising from ethnic difference was not uncommon. Kosovo, former province of Serbia is a case in point. The roots of Serbian and Albanian communities’ conflict regarding Kosovo dated back since the medieval period after the conquest of Kosovo by Serbs. The primary cause may not be ethnicity, rather it is political but once conflict happen ethnic identity and history will play pivotal role to manipulate and galvanize support for each parties cause. This article try to assess the interplay between ethnic identity and conflict resulting the rise of dangerous ethno-nationalism in Yugoslavia and contributing repressive violent action against its majority Albanian province, Kosovo and its eventual declaration of unilateral independence.